Fas/CD95 Ligation Induces Proliferation of Primary Fetal Astrocytes Through a Mechanism Involving Caspase 8-Mediated ERK Activation - Olga Barca; Marcos Seoane; Rosa Mª Señarís; Víctor M. Arce (Cellular Physiology and Biochemistry, 2013)
Background: Fas/CD95 is the best-studied member of the death receptor (DR) superfamily in the central nervous system where it can trigger cellular responses other than apoptosis, including the promotion of neurogenesis and neuritogenesis, stimulation of the progression of gliomas, and regulation of the immune response of astrocytes. Methods: We have investigated the role of Fas/CD95 in the regulation of the proliferation of fetal astrocytes in vitro, as well as the signalling pathways involved. Results: Fas/CD95 ligation stimulated the proliferation of primary fetal astrocytes, through a mechanism that depends on the activation of caspase 8 and subsequent phosphorylation of extracellular signal regulated kinase (ERK). Interestingly this proliferative effect is only observed with a low dose of the Fas/CD95 agonist. In contrast, when primary astrocytes are challenged with a high dose of the Fas/CD95 agonist significant cell death occurs. Conclusions: Our findings support that, besides its effects on cell survival, Fas/CD95 may play a complex and prominent role in the regulation of astrocyte proliferation during development.